EXPERIMENTAL INVESTIGATION AND OPTIMIZATION OF THERMODYNAMIC PROPERTIES AND PHASE DIAGRAMS IN THE SYSTEMS CAO-SIO2, MGO-SIO2, CAMGSI2O6-SIO2 AND CAMGSI2O6-MG2SIO4 TO 1.0 GPA - Hudon P.; Jung In.Ho.; Baker D.R. (My University, 2005)
Using experimental results at 1.0 GPa for the systems CaO–SiO2, MgO–SiO2, CaMgSi2O6–SiO2 and CaMgSi2O6–Mg2SiO4, and all the currently available phase equilibria and thermodynamic data at 1 bar, we have optimized the thermodynamic properties of the liquid phase at 1.0 GPa. The new optimized thermodynamic parameters indicate that pressure has little effect on the topology of the CaO–SiO2, CaMgSi2O6–SiO2, and CaMgSi2O6–Mg2SiO4 systems but a pronounced one on the MgO–SiO2 binary. The most striking change concerns passage of the MgSiO3 phase from peritectic melting at 1 bar to eutectic melting at 1.0 GPa. This transition is estimated to occur at 0.41 GPa. For the CaMgSi2O6–SiO2 and CaMgSi2O6–Mg2SiO4 pseudo-binaries, the size of the field clinopyroxene + liquid increases with increasing pressure. This change is related to the shift of the piercing points clinopyroxene + silica + liquid (from 0.375 mol fraction SiO2 at 1 bar to 0.414 at 1.0 GPa) and clinopyroxene + olivine + liquid (from 0.191 mol fraction SiO2 at 1 bar to 0.331 at 1.0 GPa) that bound the clinopyroxene + liquid field in the CaMgSi2O6·SiO2 and CaMgSi2O6·Mg2SiO4 pseudo-binaries, respectively.